Analisis Literatur Tentang Hukum Kirchoff Dalam Desain Rangkaian Listrik Modern - Lase, Dermawanda; mendrofa, joice sritari (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study examines the relevance and application of Kirchhoff's Laws in modern electrical circuit design and their impact on everyday life, especially on technology that is often used by the community. Kirchhoff's Laws, consisting of Current Law (KCL) and Voltage Law (KVL), provide basic principles for analyzing current and voltage in electrical circuits, which are the foundation for various modern devices such as smartphones, computers, medical devices, and electric vehicles. In an era of sophisticated technology, these devices must operate efficiently and safely in increasingly miniature sizes but with high computing power. The use of formulas with a fairly long calculation process and the many mathematical equations used to analyze electrical circuits make students find it difficult to study electrical circuit courses. In other words, Kirchhoff's Laws are not only theoretical principles, but also important foundations that ensure the reliability and performance of electronic devices that are increasingly essential in modern life. The research method used in the journal is literature study The results of the study show that the application of Kirchhoff's Laws and Ohm's Laws can be applied to make it easier to analyze an electrical circuit.